2022
DOI: 10.1024/1010-0652/a000322
|View full text |Cite
|
Sign up to set email alerts
|

Kann erlebte Unterstützung durch Lehrkräfte schulische Erschöpfung und Stress bei Schülerinnen und Schülern abfedern?

Abstract: Zusammenfassung. Im Laufe der Schuljahre berichten Sekundarschülerinnen und -schüler zunehmend hohe Stress- und Erschöpfungswerte, die den Bildungserfolg und die Gesundheit gefährden. Die Puffer-Hypothese hat gezeigt, dass soziale Unterstützung die Wahrnehmung von Stress abfedern kann. Allerdings wurde das Unterstützungsverhalten der Lehrkräfte unter Berücksichtigung längsschnittlicher Studiendesigns in diesem Zusammenhang selten untersucht und bislang nicht weiter ausdifferenziert. Diese Forschungslücke aufgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Hence, if a student perceives teachers as supportive, this student experiences less stress, as he/she applies coping strategies to deal with stressors and reports lower helplessness. These findings are in line with previous correlational and longitudinal studies that investigated the direct paths of the predictor variables teacher support (Hughes, 2012;Hoferichter and Raufelder, 2021) for students' stress level. Contrary to H1, however, no significant relationship was found between teacher support and grades.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Hence, if a student perceives teachers as supportive, this student experiences less stress, as he/she applies coping strategies to deal with stressors and reports lower helplessness. These findings are in line with previous correlational and longitudinal studies that investigated the direct paths of the predictor variables teacher support (Hughes, 2012;Hoferichter and Raufelder, 2021) for students' stress level. Contrary to H1, however, no significant relationship was found between teacher support and grades.…”
Section: Discussionsupporting
confidence: 92%
“…Students' academic achievement is conceptualized by students' grades in the subjects German, Math, and English. So far, there have been some empirical studies investigating the single paths on how peer support and/or teacher support relate to students' stress, while others have focused on how social support relates to students' achievement (e.g., Tennant et al, 2015;Hoferichter and Raufelder, 2021;Hoferichter et al, 2021a). Although COR provides a framework for how social support may be related to student stress and academic achievement, it has not been empirically quantified how peer support as well as teacher support relate to students' stress and academic achievement on an individual (student) and contextual (classroom) level.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A teacher’s praise influences the learning environment in a positive way, thus contributing substantially to the classroom climate longitudinally (Ingemarson et al, 2020). In addition, studies have shown that a teacher’s praise can enhance students’ learning and prosocial behavior, as well as contribute to a positive learning environment and reduce stress and school burnout (Cimpian et al, 2007; Gable et al, 2009; Hoferichter & Raufelder, 2022; Zentall & Morris, 2012). Overall, research studies until now have shown that the relationship aspect is more prominent than the interaction aspect (Schlesier, 2020).…”
Section: Introductionmentioning
confidence: 99%